Adaptation and embedding of modern military objects on the example of the Kłodzko Fortress - Drobek, Katarzyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The issue of adaptation and modernization of fortifications is very important nowadays. Military objects have lost their original purpose and have largely been left alone. Recently there has been a constant increase in interest in the military. This causes that more and more such objects are being adapted to the new function. This is the only way to protect them from degradation. An excellent example of this type of objects is the Kłodzko Fortress, which belongs to the best preserved and most impressive Silesian fortifications and is a unique example of military architecture on a Polish scale. After it was abandoned by the military, the technical condition of the object significantly deteriorated. The reason for that were attempts to introduce new functions to it. Currently, works are being carried out in order to remove some of the secondary layers. However, in order for the object to function properly nowadays it is necessary to create a plan for its modernization, which would cover the whole Fortress. Gradual changes would ensure efficient functioning and its development in the future.